2005
DOI: 10.1161/01.hyp.0000175475.17666.26
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Prostacyclin Is an Autocrine Regulator of Arterial Baroreceptor Activity

Abstract: Abstract-We tested the hypothesis that neuronal prostacyclin is an autocrine regulator of arterial baroreceptor neuronal activity. In isolated rat aortic nodose baroreceptor neurons, mechanical stimulation depolarized 12 neurons by 13.1Ϯ3.4 mV and triggered action potentials in 5 of them, averaging 18.2Ϯ9.5 spikes. Current injections depolarized 21 neurons by 29.9Ϯ8.0 mV and triggered action potentials averaging 17.0Ϯ2.4 spikes. After a period of prolonged neuronal activation with pulses of 1 nA at 20 Hz for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…Therefore, we measured the production of PGI 2 in the presence of furegrelate in mesenteric arteries from both control and orchidectomized rats. First, we found that orchidectomy did not modify either the basal or EFS-induced PGI 2 release, in contrast to the increased PGI 2 formation observed in aorta from comparable animals (Martorell et al 2008); these results are in line with reports showing smooth muscle (Wang et al 1993, Ferrer et al 2004) and/or neuronal (Snitsarev et al 2005) cells as cellular sources of PGI 2 . Concerning the effect of endogenous TXA 2 on PGI 2 production, we observed that the inhibition of the endogenous TXA 2 synthesis did not modify the release of PGI 2 in arteries from control rats, although it did increase PGI 2 release in arteries from orchidectomized rats.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we measured the production of PGI 2 in the presence of furegrelate in mesenteric arteries from both control and orchidectomized rats. First, we found that orchidectomy did not modify either the basal or EFS-induced PGI 2 release, in contrast to the increased PGI 2 formation observed in aorta from comparable animals (Martorell et al 2008); these results are in line with reports showing smooth muscle (Wang et al 1993, Ferrer et al 2004) and/or neuronal (Snitsarev et al 2005) cells as cellular sources of PGI 2 . Concerning the effect of endogenous TXA 2 on PGI 2 production, we observed that the inhibition of the endogenous TXA 2 synthesis did not modify the release of PGI 2 in arteries from control rats, although it did increase PGI 2 release in arteries from orchidectomized rats.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, we observed a slight but continuous increase in MAP in the iloprost-treated group under physiological conditions. The reason for this might be that PGI 2 is an autocrine regulator of arterial baroreceptor neuronal activity [42] and might alter the set point, and thereby promote this MAP increase. Taken together, topical application is a safe method to improve regional microcirculation without systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, prostaglandins-both those released from the endothelium and those released from baro receptor neurons themselves-serve as paracrine and autocrine modulators of baroreceptor activity. 11,12 Prostacyclin provides autocrine feedback that restores the responsiveness of arterial baroreceptor neurons after their inhibition from excessive neuronal activation, as with increased BP. Reduced synthesis of neuronal prostacyclin might contribute to resetting and impaired activity of arterial baroreceptors in NSAID-induced hypertension.…”
Section: Arterial Baroreflex Arcmentioning
confidence: 99%